Aging and Self-Regulated Language Processing. [article]. - Stine-Morrow, Elizabeth A. L..
An adult developmental model of self-regulated language processing (SRLP) is introduced, in which the allocation policy with which the reader engages text is driven by declines in processing capacity, growth in knowledge-based processes, and age-related shifts in reading goals. Evidence is presented to show that the indicidual reader's allocation policy is consistent across time and across different types of text, can serve a compensatory function in relation to abilities, and is predictive of subsequent memory performance. as such, it is an important facet of language understanding and learning from text through the adult life span. -- (from the author)
Keywords: Language processing; Text memory; Cognitive aging; Self-regulation.; Compensation